All is flux: the predictive power of fluctuating Quaternary mammalian faunal-climate scenarios - Schreve, Danielle (Philos Trans R Soc Lond B Biol Sci, 2019)
The long-term impact of Middle and Late Pleistocene glacial-interglacial change led to the major reorganization of mammalian faunal communities in northern Europe through species origination, extinction, evolutionary change and distributional shifts. A Bray–Curtis cluster analysis with single linkage to examine relative faunal similarity was performed on mammalian assemblages from five successively older interglacials (MIS 1, 5e, 7c-a, 9 and 11) in Britain, a region with an exceptionally well-resolved faunal record for this time period. The results indicate a degree of continuity in terms of common interglacial elements occurring across all periods but also reveal that the particular climatic and environmental parameters of each interglacial resulted in the generation of very different faunal assemblages, depending on the length, intensity and structure of the interglacial. Of particular note are the comparability of the mammalian assemblages from warm interglacials MIS 5e and 9, and the high species diversity seen in MIS 7c-a, linked to relatively cool temperate conditions and the spread of dry grasslands. Together, these results offer insight into the overall ‘predictability' of Quaternary mammalian interglacial community composition and what might be expected in the natural evolution of a Holocene interglacial freed of anthropogenic interference. This article is part of a discussion meeting issue ‘The past is a foreign country: how much can the fossil record actually inform conservation?’